2013
DOI: 10.1055/s-0032-1328438
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for Patients with Early Breast Cancer and its Impact on Quality of Life - a Randomized Controlled Trial

Abstract: Introduction !Breast cancer is the most common malignancy in women worldwide. It accounts for 14 % of all cancer diagnoses in Europe [1]. In the industrialized countries of the northern hemisphere, between one in eight and one in ten women will be diagnosed with breast cancer in their lifetime [2,3]. Due to the enormous advances in adjuvant and palliative treatment, it has, in many cases, become a controllable chronic disease [4]. Abstract !The aim of this prospective, randomized, controlled trial was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
1
25
0
2
Order By: Relevance
“…The use of yoga for depression and mood disturbance was downgraded from grade A to grade B because of 4 new published studies demonstrating conflicting results . The use of yoga for improving QOL changed from grade C to grade B, because 2 additional trials demonstrated beneficial effects . Finally, new trials on the use of yoga and hypnosis for fatigue upgraded previous recommendations from grade I to grade C.…”
Section: Literature Review On the Use Of Complementary And Integrativmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of yoga for depression and mood disturbance was downgraded from grade A to grade B because of 4 new published studies demonstrating conflicting results . The use of yoga for improving QOL changed from grade C to grade B, because 2 additional trials demonstrated beneficial effects . Finally, new trials on the use of yoga and hypnosis for fatigue upgraded previous recommendations from grade I to grade C.…”
Section: Literature Review On the Use Of Complementary And Integrativmentioning
confidence: 99%
“…Yoga is recommended for improving QOL in patients with breast cancer (grade B). This recommendation is based on 12 RCTs, completed between 2006 and 2015, which tested a variety of yoga programs (see Supporting Information Table 4) . QOL was the primary outcome for 6 of those 12 trials .…”
Section: Literature Review On the Use Of Complementary And Integrativmentioning
confidence: 99%
“…Reviews and metaanalyses evaluating the effect of yoga in randomised controlled trials (RCT) in women with breast cancer conclude there is moderate to good evidence that yoga may be a useful practice during recovery from treatment [11][12][13]. Despite an emerging number of large RCTs measuring the effectiveness of yoga on fatigue [14,15], sleep quality [16], QoL [17], and during radiotherapy [18], there is scope for more investigation into its physical benefits, in particular its role following breast cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, personality traits (extraversion vs. introversion) have been identified to show different gene expression profiles related to proinflammatory signaling [27]. It is also known that stress-release programs, ethical caring, choir singing, and psychotherapy have beneficial effects on women with breast cancer [28,29,30,31], and an important stress-reducing aspect of anthroposophic care is the individually composed therapy consisting of holistic care including natural products, Iscador, diets, art therapy, rhythmic therapy, therapeutic massage, and hydrotherapy [3,4]. A deeper psychoneuroimmunological understanding of these effects induced by intervention programs are needed [32].…”
Section: Discussionmentioning
confidence: 99%